Impact of price-related factors on electric vehicle adoption in Singapore - Lim, Andrea Zhi Xuan (Nanyang Technological University, 2023)
In its ambition to achieve net zero emissions by 2050, the Singapore government has introduced a series of price-related policies, including tax rebates under the Early Adoption Incentive and carbon rebates via the Enhanced Vehicular Emissions Scheme, to promote consumer adoption of electric vehicles (EVs). However, consumer demand for EVs in Singapore remains low at a 12% penetration rate as of 2022. This article addresses the need for an empirical investigation of factors affecting private demand for EVs and the efficacy of government policies introduced to promote EV uptake in Singapore. Difference-in Difference and Panel Fixed Effects regression models were used to test the relationship between price related factors (specifically fiscal incentives, gasoline prices and electricity prices) and new EV registrations in Singapore. Evidence from our analysis revealed an economically and statistically significant relationship between EV sales and price-related factors. The findings in this paper affirm the current policy instruments used by the government in promoting the diffusion of EVs in Singapore.